ISO 27000 and KAMI Index: PT XYZ (Travel Agent) - Gavrilla Claudia; Wella Wella (Universitas Multimedia Nusantara, 2023)
PT XYZ is one of the Travel Agent companies in Indonesia that is aware the value of information security, as shown due to the ISO 27001:2013 certification in 2021. However, there are still areas that must be adjusted to improve the company's Information Security Management System. In this study, the CAPD (Check-Act-Plan-Do) technique was used, with the KAMI Index supporting as an information security evaluation tool in compliance with ISO 27001:2013 standards. Check examines the firm's present state, Act evaluates the areas identified in the KAMI Index, Plan analyzes the evaluation outcomes and makes recommendations in accordance with ISO 27001: 2013 and Do offers recommendations to the company. The results of the evaluation show that PT XYZ received a score of 623 from 645 and the value is in the green area, indicating that it is in the